PENERAPAN PENGELOLAN TANAMAN TERPADU (PTT) PADI SAWAH DI KECAMATAN KEBASEN KABUPATEN BANYUMAS - WATEMIN WATEMIN; SULISTYANI BUDININGSIH (Universitas Sebelas Maret, 2012)
This research aim to know the level of Pengelolaan Tanaman Terpadu (PTT) of paddy field in Subdistrict of Kebasen Banyumas Regency. Research conducted by using description method. Location of the research choice by purposive sampling with the consideration that research location represent the first area multiply to apply PTT in Banyumas Regency. Sample taken as much 60 farmer by using method of simple random sampling. Research data obtained through by interview to the sample. Hereinafter research data analysed by using percentage calculation to existing indicator of PTT. Result of research indicate that the level of applying PTT paddy field as a whole equal to 76,67%.